The role of incentive to raise production efficiency - Fatima D. Malooh (Journal of Madenat Alelem University College, 2014)
Management incentives in the work have a privileged position in the pay of the individual to work efficiently. We find that the recent studies have increased concerns the process of motivating employees and creating a desire to have in collaborative work to create the motivation of the individual in the same interior and there directing his actions and behavior towards the target set by the organization and perhaps the most important motives are Human feeling the need to something specific. The individual is trying to search for what insatiable need those incentives represent the means available to the organization to satisfy the needs of missing. The study divided to two sections and a number of demands addressed subsection called the first part deals with what is the incentives and their importance within the four demands the first specified to introduce incentives and theory needs either second requirement has been deald the benefits of incentives and disadvantages of dealing the third demand study the system of incentives and methods of organization and modern search requirement fourth study, training and theory of incentives. The second part, have discussed non formal organize of incentives. The theory of incentives have been divided into four demands devoted the first of it to study non formal organized Alasm groups. The second requirement theory of incentives and influence on human behavior and discussed in the third demand theory of incentives and administrative leadership, and finally address the requirement fourth cases of non-possibility of the use of incentives human.